Dimensions that influence the innovation process in justice organizations - Marilú Pereira Castro; Tomas Aquino de Guimaraes (Innovation & Management Review, 2020)
Purpose - The purpose of this paper is to identify dimensions that can influence the innovation process in justice organizations. Design/methodology/approach This study uses a qualitative approach. Data were collected through a semi-structured interview script. In all, 23 in-depth interviews were undertaken with lawyers, public defenders, judges, prosecutors and public officials from the five regions of Brazil. These data were analyzed using content analysis techniques. Findings The perceptions of the interviewees show that the process of innovation in justice organizations can be influenced by five dimensions: Institutional Environment (institutional level), Leadership (organizational level), Organizational Resources (organizational level), Cooperative Relations (interorganizational level) and Innovative Behavior (individual level). These dimensions may promote or restrict innovation. Originality/value The results indicate that there are growing efforts to introduce innovations designed to improve the performance and service delivery of justice organizations. However, there is resistance to innovation because these organizations are highly institutionalized and consequently seek stability and absence of change.
Keywords: 650; Administration of justice; Innovation in justice; Justice organizations